An Evidence-Based Review on Wound Healing Herbal Remedies From Reports of Traditional Persian Medicine - Hosseinkhani, Ayda (J Evid Based Complementary Altern Med, 2016)
Research on wound healing agents is a developing area in biomedical sciences. Traditional Persian medicine is one of holistic systems of medicine providing valuable information on natural remedies. To collect the evidences for wound-healing medicaments from traditional Persian medicine sources, 5 main pharmaceutical manuscripts in addition to related contemporary reports from Scopus, PubMed, and ScienceDirect were studied. The underlying mechanisms were also saved and discussed. Totally, 65 herbs used in traditional Persian medicine for their wound healing properties was identified. Related anti-inflammatory, antioxidant, antimicrobial, and wound-healing activities of those remedies were studied. Forty remedies had at least one of those properties and 10 of the filtered plants possessed all effects. The medicinal plants used in wound healing treatment in traditional Persian medicine could be a good topic for further in vivo and clinical research. This might lead to development of effective products for wound treatment.